The Impact of Reaction Pressure on the Catalytic Performance of the PdSb/TiO2 Catalyst in the Acetoxylation of Toluene into Benzyl Acetate. Issue 1 (26th October 2012) - Madaan, Neetika; Gatla, Suresh; Kalevaru, Venkata Narayana; Radnik, Jörg; Pohl, Marga‐Martina; Lücke, Bernhard; Brückner, Angelika; Martin, Andreas
Abstract The acetoxylation of toluene in the presence of acetic acid and oxygen was performed over a PdSb/TiO2 catalyst at 210 °C and at various reaction pressures (1–10 bar). A remarkable improvement in the catalytic performance and a significant shortening of the induction period were found with an increase in pressure. At a pressure of 6 bar, the highest toluene conversion of 75 % and 100 % selectivity for benzyl acetate were observed. This result could be due to both the restructuring of the catalyst surface and to the formation of active PdSb particles of desired size, composition, and shape during the course of the induction period. Samples of the most‐active and spent catalysts were studied by ex situ and in situ XRD, XPS, and TEM.